An insight into the mechanical behavior of adhesively bonded plain-woven-composite joints using multiscale modeling. (1st April 2022) - Hou, Yuliang; Wang, Weihan; Meng, Liang; Sapanathan, Thaneshan; Li, Jishuai; Xu, Yingjie
Abstract: The mechanical behavior of adhesively bonded plain-woven-composite (PWC) joints has been investigated using a multiscale modeling approach. Microscale and mesoscale representative volume elements (RVEs) have been constructed using the hierarchical architectures of PWCs. Based on the local homogenization of the mesoscale RVE model, an equivalent cross-ply laminate (ECPL) cell is developed to represent the woven architecture. It enables not only to accurately compute the effective properties of PWCs, but also to efficiently retain the local behavior within each ply. The macroscale models of single-lap joints (SLJs) and double-lap joints (DLJs) fabricated with PWCs, are constructed by topologically arraying the ECPL cells. Combined with continuum damage mechanics (CDM) and cohesive zone model, the mechanical behaviors are predicted for the SLJs and DLJs subjected to tensile loads. Moreover, experimental tensile tests have been performed on the corresponding SLJ structures, which confirm the reliability of the proposed multiscale models. A parametric study of the overlap length and width, as well as the bondline thickness has been numerically carried out to further analyze their effect on the joining performance. It reveals that, the dominant damage mechanisms mainly depend on the overlap length. When the overlap length is less than a critical value, the main damage mode is identified as the debonding of the bondlines. Otherwise, the delamination and matrix-tensile damages within the composite adherends are considered as the dominant damage modes. Graphical abstract: Highlights: A multiscale modeling approach is proposed for adhesively bonded PWC joints. An ECPL cell is used to simplify the woven structure based on local homogenization. The proposed approach is validated by tensile tests on different single-lap joints. The effect on the joining performance is analyzed for various design parameters. The damage mechanisms are identified for SLJs and DLJs using multiscale modeling.